Response of Some Medicinal Plants to Vesicular Arbuscular Mycorrhizal Inoculations - Karthikeyan, B.; Joe, M. M.; Cheruth, A. J. (Journal of Scientific Research, 2009)
An investigation has been made about the response of vesicular arbuscular mycorrhizal fungi of G. fasciculatum on some medicinal plants. Medicinal plants species selected for the study are Ocimum sanctum, Catharanthus roseus, Coleus forskholii and Cymbopogon flexuosus. The percentage of VAM association is 85 and the intensity of formation of vesicles and arbuscules are 70% and 30%, respectively in VAM inoculated C. roseus plants. The total dry matter production (shoot and root dry wt), protein and total chlorophyll contents are seen to increase in VAM inoculated plants. The percentage of increase is more in C. roseus, followed by Cymbopogon flexosus when compared to control plants. Keywords: Ocimum sanctum, Coleus forskholii, Cymbopogon flexosus, Catharanthus roseus, VAM fungi. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1675